Assessment of risk of loss of the implant in two-stage breast reconstruction - E. V. Shivilov; G. E. Kvetenadze; Kh. S. Arslanov; O. E. Tseplina (Опухоли женской репродуктивной системы)
Surgical treatment remains one of the leading methods in the treatment of breast cancer. Every year, the number of breast reconstruction operations is steadily increasing. But the number of possible complications associated with performing such operations also increases. Breast reconstruction using an expander may be one of the acceptable options for patients who are planning radiation therapy. The article analyzes the results of two-stage reconstructive plastic surgery on the breast in the complex treatment of patients diagnosed with breast cancer. In 90.5 % of cases, a good cosmetic result was obtained. The risk of losing the implant after chemotherapy was 4.8 % and 13.9 % for chemotherapy combined with radiation therapy, respectively. Two-stage breast reconstruction can be used with careful selection of patients.